2007
DOI: 10.1111/j.1467-6494.2007.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Development From Late Adolescence to Young Adulthood: Differential Stability, Normative Maturity, and Evidence for the Maturity‐Stability Hypothesis

Abstract: This investigation examined personality development during the transition from adolescence to adulthood using the brief form of the Multidimensional Personality Questionnaire (Patrick, Curtin, & Tellegen, 2002). Parent and self-reports of personality were obtained in 1994 (average age=17.60 years), and self-reports were obtained in 2003 (average age=27.24 years). There was evidence of both differential stability and normative changes in the direction of increased functional maturity during this transition. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
175
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 45 publications
18
175
2
3
Order By: Relevance
“…Roberts et al (2001) also found that, in terms of the individual-level change from age 18 to age 26, a vast majority of participants (89%) remained at the same level of risk propensity; only 5.0% had decreased and 5.9% had increased in risk propensity. Using a separate sample, Donnellan et al (2007) found highly similar results as Roberts's et al (2001) study. Based on these empirical findings on the stability of risk propensity from adolescence to young adulthood, we believe that our measure of risk propensity is a reliable proxy of risk propensity in adolescence.…”
Section: Risk Propensitysupporting
confidence: 88%
“…Roberts et al (2001) also found that, in terms of the individual-level change from age 18 to age 26, a vast majority of participants (89%) remained at the same level of risk propensity; only 5.0% had decreased and 5.9% had increased in risk propensity. Using a separate sample, Donnellan et al (2007) found highly similar results as Roberts's et al (2001) study. Based on these empirical findings on the stability of risk propensity from adolescence to young adulthood, we believe that our measure of risk propensity is a reliable proxy of risk propensity in adolescence.…”
Section: Risk Propensitysupporting
confidence: 88%
“…Studies suggest stability of certain aspects of brain connectivity (Cao et al, 2014;Poppe et al, 2013) while other studies have reported a certain amount of plasticity in brain connectivity (Scholz et al, 2009). Lifespan studies on personality indicate that personality changes over the lifespan, particularly during maturation from adolescence to early adulthood (Blonigen, Carlson, Hicks, Krueger, & Iacono, 2008;Roberts, Caspi, & Moffitt, 2001), and that some changes in traits depends on the personality profile at younger age (Donnellan, Conger, & Burzette, 2007;Lönnqvist, Mäkinen, Paunonen, Henriksson, & Verkasalo, 2008). Longitudinal studies on personality and brain connectivity are still outstanding.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research among adolescents may reflect controversies regarding the diagnosis of personality pathology in adolescents. Although research has found that personality disorders occur frequently and can be reliably diagnosed in adolescents [12], research suggesting that personality does not typically coalesce before adulthood [13] coupled with concerns about stigma and other long-term impacts of personality-related diagnoses has contributed to clinician reticence to diagnose adolescents with personality disorders. However, recent research suggests that personality disorders are valid clinical markers in adolescents [14], although personality disorders manifest even worse comorbidity problems in this group than they do in adults [8,15].…”
Section: Introductionmentioning
confidence: 96%